a. Recall the double angle identities:
[tex]\sin^2x=\dfrac{1-\cos2x}2[/tex]
[tex]\cos^2x=\dfrac{1+\cos2x}2[/tex]
Then
[tex]\sin^2x\cos^2x=\dfrac{(1-\cos2x)(1+\cos2x)}4=\dfrac{1-\cos^22x}4[/tex]
Applying the identity again, we have
[tex]\sin^2x\cos^2x=\dfrac{1-\frac{1+\cos4x}2}4=\dfrac{2-(1+\cos4x)}8=\dfrac{1-\cos4x}8[/tex]
as required.
b. Using the result from part (a),
[tex]\sin^2x\cos^2x=\dfrac{1-\cos4x}8=\dfrac{2-\sqrt2}{16}[/tex]
[tex]\implies\cos4x=\dfrac1{\sqrt2}[/tex]
[tex]\implies4x=\dfrac\pi4+2n\pi\text{ or }4x=-\dfrac\pi4+2n\pi[/tex]
(where [tex]n[/tex] is any integer)
[tex]\implies\boxed{x=\pm\dfrac\pi{16}+\dfrac{n\pi}2}[/tex]